Biliary atresia in preterm infants: a single center experience and review of literature - Beati, Federico; Mosca, Antonella; Pietrobattista, Andrea; Liccardo, Daniela; Ronci, Sara; Monti, Lidia; Francalanci, Paola; Spada, Marco; Maggiore, Giuseppe; Bagolan, Pietro; Fusaro, Fabio (Frontiers in Surgery, 2024)
Introduction The diagnosis of biliary atresia (BA) remains challenging, and there is still uncertainty regarding the optimal time to perform a Kasai portoenterostomy (KPE). Little is known about the difficulties in the diagnosis and outcomes of BA in preterm infants (PBA). This study, which represents the first Italian report of preterm infants with BA, aims to describe a single-center experience of BA in preterm newborns. Methods We retrospectively reviewed all infants consecutively diagnosed with BA who underwent a Kasai procedure at the Bambino Gesù Children’s Hospital between January 1998 and December 2021. Prematurity was defined as a gestational age (GA) of <37 weeks. Demographic, laboratory, and histology data were recorded, and the main outcomes considered were clearance of jaundice (COJ), native liver survival, and mortality. Results A total of 21 PBA were compared with 117 term BA controls (TBA). The median GA of PBA was 35.1 (32–36.1) weeks, with a mean birth weight of 2,100 (1,897–2,800) g. Age at first presentation was significantly lower in PBA patients: 46 (22–68) vs. 61 (44–72) days; p = 0.02. The median age at KPE was similar between the two groups: 70 days (33 corrected) for PBA vs. 67 in TBA; p = 0.8. At the time of surgery, median serum bilirubin was lower in the PBA group (7.7 vs. 8.6 mg/dl, p = 0.04). Similarly, the median APRi at the time of KPE was lower but not significant in the PBA group: 1.09 vs. 1.16; p = 0.8. No differences were found in terms of COJ between the PBA and TBA groups: n = 9 (43%) vs. 34 (35%); p = 0.2. Overall native liver survival was similar between the two groups: 8.6 (4.8–12.2) for the PBA group vs. 7.6 (5.6–9.5) years for the TBA group with no significant differences; p = 0.45. Post-KPE native liver survival was similar between the two groups: 38% vs. 52% at 5 years for the TBA and PBA groups, respectively; p = 0.54. Conclusion The PBA and TBA groups appear to have similar outcomes in terms of COJ, overall native liver survival, and 5-year liver survival. Considering the corrected GA, early KPE is related to lower cholestatic damage. Further multicenter studies are required.